Understanding accident investigators : a study of the required skills and behaviours for effective UK inspectors of accidents - Flaherty, Sarah (Cranfield University, 2008)
In the UK, accidents associated with maritime, aviation and rail transport are conducted by the Inspectors of Accidents at the Marine, Air and Rail Accident Investigation Branches. A review of current academic literature provides little insight into the qualities and attributes essential for the role of accident investigator. A wealth of material exists about accidents themselves but as yet, a study into the profile of the accident investigator has not been conducted. This research sought to determine the requisite skills and behaviours of an effective accident investigator based upon a three-phased, primarily qualitative, methodology. Content analysis was used to determine task and non-task specific themes from semistructured interviews conducted with accident investigators from the UK and the US, the findings of which are characterized by individualism and variability: the former having implications for effective teamwork and the latter indicating the paucity of structured analysis processes in use, which would lead to reproducible and transparent results. Repertory Grid interviews elicited five competency themes and one hundred attendant behavioural indicators which were employed during the final phase of the research to determine their relative importance in terms of recruitment, training and the superior investigator. The findings showed that it was believed essential to consider interpersonal and communication skills, cognitive abilities and personal attributes during recruitment and that technical skills were deemed to be most amenable to change through training interventions with personal abilities least likely. Further thematic analysis of highly rated behavioural indicators showed an emphasis on report writing and dealing with people. These findings have implications for recruitment with a need for non-technical competencies such as report writing and the ability to deal with people to be more prevalent in selection testing and decision-making. No specific skills or behaviours were found to distinguish superior performance in investigation, instead requiring a balance of competencies. With no defining threshold, the researcher proposed that superior performance should be measured "relative to mission" and is more usefully thought of an added value continuum rather than a set of discrete skills and behaviours. Evidence was provided to demonstrate how the organizational structure and philosophy influenced the working styles of the Inspectorate and therefore the expected skills and behaviours. The researcher advocates the combination of the competency framework and behavioural indicators derived with an extant Branch competence measure to strengthen the tools whilst responding to a call in the literature for a more blended approach to determining competences and competencies.